A new species of the genus Euricania Melichar, 1898 (Hemiptera: Fulgoromorpha: Ricaniidae) from China, with a world checklist and a key to all species recorded for the country - Ren, Lan-Lan; Stroiński, Adam; Qin, Dao-Zheng (Zootaxa, 2015)
One new species of the planthopper genus Euricania Melichar, 1898 – E. paraclara sp. nov. is described from Guizhou (southwest China). A checklist of all Euricania species and an identification key to the species of the Chinese fauna are provided. Photographs of the adult and illustrations of male and female genitalia of the new species are also given.